Linguodidactic Potential of Precedent Texts in Literary Discourse: Methodological Approaches to Teaching Russian as a Foreign Language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This research reveals and characterizes the linguodidactic potential of studying precedent texts in literary discourse in Russian as a foreign language classes. The linguistic personality is described as an object of linguodidactics with emphasis on the specificity of understanding and using precedent texts as markers of linguistic personality development level. The article develops a system of tasks based on precedent texts from literary discourse aimed at expanding students' sociocultural horizons. It has been established that a linguistic personality represents a multilayered and multicomponent set of linguistic abilities, skills, and readiness to perform speech acts of varying complexity, considering the formation of personal, value (worldview), and culturological components. The study reveals that the most important characteristic of a linguistic personality is the level of language proficiency, which presupposes knowledge of linguistic units and the ability to use them in accordance with national-cultural traditions and communication situations. It has been proven that one of the most significant indicators of linguistic personality formation level is mastery of precedent texts - names, utterances, cultural symbols that are significant for the individual and society. The proposed methodology for working with precedent texts involves gradual task complexity: from simple exercises on meaning comprehension to creative tasks on interpretation and independent use of precedent texts in speech. The research demonstrates that systematic work with precedent texts contributes to expanding students' vocabulary, developing logical thinking and memory, and forming sociocultural and communicative competencies.
Keywords: linguistic personality; precedent text; precedent cultural phenomenon; Russian as a foreign language; linguodidactics; literary discourse; sociocultural competence; intercultural communication